2022
DOI: 10.5935/1518-0557.20210049
|View full text |Cite
|
Sign up to set email alerts
|

Surgical approach to uterine myomatosis in patients with infertility: open, laparoscopic, and robotic surgery; results according to the quantity of fibroids

Abstract: Objective To compare approaches to myomectomy (laparotomic, laparoscopic, and robotic). To show the relationship between the number of fibroids and the reproduction diagnosis. Methods Observational, analytical, retrospective, and cross-sectional study; where the surgical approach used, was evaluated in terms of surgical bleeding, time, number and weight of fibroids and reproductive results. Results 69 patients were treated through different a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…A total of 1219 articles were obtained, and after eliminating duplicates by Endnote X9, and then eliminating irrelevant papers by reading the title and abstract, 15 articles were retained after reading the full text [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. See Table 1 for basic information on the selected literature.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 1219 articles were obtained, and after eliminating duplicates by Endnote X9, and then eliminating irrelevant papers by reading the title and abstract, 15 articles were retained after reading the full text [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. See Table 1 for basic information on the selected literature.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…The results [MD=-24.67, 95%CI (-41.91, -7.43), P=0.005] indicate a statistically signi cant difference between the two surgical approaches in terms of intraoperative bleeding, suggesting that the RALM group had less intraoperative bleeding than the LM group, the results of the Meta-analysis are shown in Figure3. P=0.01] indicate a statistically signi cant difference in the incidence of blood transfusions between the two procedures, suggesting that fewer people in the RALM group required blood transfusions than in the LM group, the results of the Meta-analysis are shown in Figure4.Comparison of transit open belly ratesA total of 11 studies were included [8-17,22] with a total of 45,092 patients, 11,347 patients in the RALM group and 33,745 patients in the LM group.Statistical heterogeneity between studies was not signi cant (P=0.32>0.1, I 2 =13%), so a xed effects model was used for data analysis. The results [OR=0.82, 95%CI (0.73, 0.92), P=0.0006] indicate a statistically signi cant difference between the two surgical approaches in terms of intermediate openings, suggesting a lower rate of intermediate openings in the RALM group than in the LM group, the results of the Meta-analysis are shown in Figure6.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The reported pregnancy rates in the current literature range from 29.1% to 77.8% with no uterine rupture [ 12 , 13 , 14 , 16 , 17 , 18 , 19 ]. Pitter et al reported a pregnancy rate of 50.8% with a follow-up of 36 months, and the uterine rupture rate in this study was 0.9% [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rates were comparable among the three groups [ 16 ]. A more recent study by Morales et al also investigated three methods and found similar clinical pregnancy rates: 29.1% in RALM, 29.1% in laparoscopic myomectomy, and 14.3% in open myomectomy [ 19 ].…”
Section: Discussionmentioning
confidence: 99%